Penerapan Metode Role Playing dalam Meningkatkan Keterampilan Berbicara Anak dan Kecerdasan Sosialnya - Moh. Hilmi (PALAPA, 2018)
This research is based on the problem of the still low social and speaking skills of children, and in general the problem of this research is "How to improve children's social and speaking skills through the application of role playing methods in the MA Assyafiiyah NW Penangsak?" the following: (1) What are the conditions of social skills and speaking skills of children before they are applied to the role playing method or role playing at the MA Assyafiiyah NW Penangsak? (2) What is the process of applying role playing methods in improving children's social skills and speaking skills at MA Assyafiiyah NW Penangsak? (3) To what extent is the improvement of social skills and speaking skills of MA Assyafiiyah NW Penangsak children after role playing or role playing methods are applied? and (4) What obstacles did the teacher experience in applying the role playing method or role playing? The goal to be achieved is to get an idea of improving social skills and speaking skills of children at MA Assyafiiyah NW Penangsak through the application of role playing methods. The research method used is Classroom Action Research (CAR) to improve the learning process of social skills and children's speaking skills through the application of role playing methods. PTK was conducted in three cycles, with the subject of children B group MA Assyafiiyah NW Penangsak, amounting to 10 children. From the results of the implementation and observations made, there was a significant increase, especially in cycle two. It is recommended for teachers so that social skills and speaking skills are further developed, both in learning, implementation and evaluation of learning. For further researchers, it is expected to be able to make research on social skills and speaking children through other methods.